ChemInform Abstract: Organocatalytic Asymmetric Synthesis of 3(2H)‐Furanones with Adjacent Quaternary and Tertiary Stereocenters. Issue 13 (1st April 2014) - He, Wujun; Jing, Linhai; Qin, Dabin; Wang, Rongming; Xie, Xiaohua; Wu, Song
Abstract Michael addition of furanones to α, β‐unsaturated ketones in the presence of a cinchona‐based chiral catalyst provides the title products (III) with high enantioselectivity and low to moderate diastereoselectivity.